Transformasi Pembelajaran Sains Kontekstual di Sekolah Dasar Pedesaan Menuju Quality Education - Malik, Muh Syauqi; Indrawati, Delia; Wati, Ika Febriana; Wardani, Helda Kusuma; Putri, Melyza Vidhia; Safitri, Devi Wahyu (Universitas Muhammadiyah Magelang, 2026)
The fundamental problem in elementary science education is the prevalence of rote learning, which creates a gap between high academic grades and low actual conceptual understanding. This phenomenon of pseudo-performance was specifically identified at Sekolah Dasar Negeri Sempol, where students achieved perfect scores through memorization but failed to explain simple scientific phenomena in their daily lives. To overcome this cognitive gap, this research implements the Contextual Teaching and Learning model, designed to connect abstract academic material with students' concrete real-world experiences. This study employs a quantitative approach with a Pre-Experimental One-Shot Case Study design, involving thirteen third-grade students selected through a total sampling technique. The novelty of this research lies in the specific use of rural environmental resources as an accessible natural laboratory to visualise abstract concepts of matter change, while simultaneously integrating the values of the Sustainable Development Goals regarding quality education and early environmental awareness. The empirical results demonstrate that this approach is highly effective. The data show that the average student learning outcome reached 96.15, with a classical mastery level of 100%. Furthermore, the analysis indicates that student enthusiasm and focus reached their peak. Although students demonstrated varying levels of understanding between concrete concepts, such as melting, and abstract concepts, such as sublimation, the overall learning process successfully transformed passive students into active knowledge constructors. This confirms that high-quality, inclusive science education can be achieved in rural schools with limited facilities.